2017
DOI: 10.3389/fncel.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Perseverative Errors during a Visual Attention Task with Auditory Distractors in Alpha-9 Nicotinic Receptor Subunit Wild Type and Knock-Out Mice

Abstract: The auditory efferent system is a neural network that originates in the auditory cortex and projects to the cochlear receptor through olivocochlear (OC) neurons. Medial OC neurons make cholinergic synapses with outer hair cells (OHCs) through nicotinic receptors constituted by α9 and α10 subunits. One of the physiological functions of the α9 nicotinic receptor subunit (α9-nAChR) is the suppression of auditory distractors during selective attention to visual stimuli. In a recent study we demonstrated that the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Two experimenters blinded to the MOC reflex strength of each animal performed the behavioural procedures. All animals were trained during ~ 3 to 4 months, five days a week, in a two-choice visual discrimination task previously used by us in rats 31,45 www.nature.com/scientificreports/ mice 18,46 . The behavioural task was performed in an operant mesh cage identical to the one used in Delano et al 9 , located inside a double-walled sound-attenuating room.…”
Section: Measurement Of Dpoaes Suppression By Contralateral Noise In mentioning
confidence: 99%
“…Two experimenters blinded to the MOC reflex strength of each animal performed the behavioural procedures. All animals were trained during ~ 3 to 4 months, five days a week, in a two-choice visual discrimination task previously used by us in rats 31,45 www.nature.com/scientificreports/ mice 18,46 . The behavioural task was performed in an operant mesh cage identical to the one used in Delano et al 9 , located inside a double-walled sound-attenuating room.…”
Section: Measurement Of Dpoaes Suppression By Contralateral Noise In mentioning
confidence: 99%
“…Other studies have adopted blocked trial designs to manipulate attention (mice: 10,96-105, rats: 106,107 ), which lend themselves more to studying the effects of selection history thereon. Yet others have employed simpler continuous performance tasks 108 to study between-subject (mice: 109,110 ), or spontaneous within-subject variations in attention (mice: 11,111-113, rats: 114,[115][116][117] ). These paradigms characterise attention using resilience to distraction 109,110,116,117 or spontaneous uctuations in responsiveness to a stimulus 11,111,[113][114][115] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is noteworthy that the present focused on the role of the EVS on reflex and motor function. Recent studies have demonstrated impairments in multisensory attention in α9 (−/−) mice during a visual selective attention task with auditory distractors ( Terreros et al, 2016 ; Jorratt et al, 2017 ). It is possible that the EVS likewise contributes to higher-order functions, for example reducing impulsivity during decision making during self-motion.…”
Section: Discussionmentioning
confidence: 99%